MARKET RESEARCH OF AIR CONDITIONERS AND HEAT PUMPS IN THE MACEDONIAN ECONOMY - Iskra Stanceva-Gigov, Klimentina Poposka (Institute of Economics-Skopje, University “Ss. Cyril and Methodius” in Skopje, Republic of North Macedonia, 2020)
The growing awareness of environmental protection and increased energy efficiency through the use of renewable energy sources, imposes the application of cooling, heating and ventilation systems based on modern technological and environmental solutions for individual homes and businesses. As the most prominent devices in the pool of new systems are heat pumps and inverters - air conditioners and their application is imposed in our country as well. Henceforth, the country will meet European standards and criteria for environmental and energy efficiency and will reap the following benefits: reducing energy demand, preserving the environment and creating a resilient renewable energy system. Hence, the aim of the paper is to assess the current market situation of these devices in the Macedonian economy and its potential, as well as to indicate the opportunities that will lead to increased sales in the market in the future. The survey is used as a method for collecting primary data for the research. Moreover the relevant secondary data sources are also utilized. The methods of analysis, synthesis, induction, deduction, as well as the logical and statistical method are used in data processing and drawing plausible conclusions. Research has clearly demonstrated that the country has made minor progress in developing this market over the years, nevertheless there is still a large number of untapped opportunities for its further advancement and full utilization.
Keywords: energy efficient solutions, environmental solutions, inverter-air conditioners, heat pumps, Macedonian market